Repeat-mediated epigenetic dysregulation of the FMR1 gene in the fragile X-related disorders - Usdin, Karen; Kumari, Daman (Frontiers in Genetics, 2015)
The Fragile X-related disorders are members of the Repeat Expansion Diseases, a group of genetic conditions resulting from an expansion in the size of a tandem repeat tract at a specific genetic locus. The repeat responsible for disease pathology in the Fragile X-related disorders is CGG/CCG and the repeat tract is located in the 5’ UTR of the FMR1 gene, whose protein product FMRP, is important for the proper translation of dendritic mRNAs in response to synaptic activation. There are two different pathological FMR1 allele classes that are distinguished only by the number of repeats. Premutation alleles have 55-200 repeats and confer risk of Fragile X-associated tremor/ataxia syndrome and Fragile X-associated primary ovarian insufficiency. Full mutation alleles on the other hand have >200 repeats and result in Fragile X syndrome, a disorder that affects learning and behavior. Different symptoms are seen in carriers of premutation and full mutation alleles because the repeat number has paradoxical effects on gene expression: Epigenetic changes increase transcription from premutation alleles and decrease transcription from full mutation alleles. This review will cover what is currently known about the mechanisms responsible for these changes in FMR1 expression and how they may relate to other Repeat Expansion Diseases that also show repeat-mediated changes in gene expression.